Czyżby przedwczesny krzyk sowy Minerwy? O renesansie syberyjskiego szamanizmu - Połeć, Wojciech (Humaniora. Czasopismo Internetowe, 2019)
In this study, I refer to the metaphor of the cry of Minerva’s owl, which was supposed to herald the twilight of a given phenomenon into the classic scientific descriptions of Siberian shamanism, which was treated by many scientists as part of the phenomenon “universal” for the history of the religion of humanity, and at the same time belonging only to the past. I am analysing the concepts of Mircea Eliade and Andrzej Wierciński in the context of my own field research on the Renaissance of Siberian shamanism. I propose a reflection on the usefulness and limitations of classical models of shamanism for studying contemporary religions of ethnic peoples traditionally considered to be shamanic. Certainly many researchers have become interested in issues related to shamanism thanks to the suggestive descriptions of the classics. The classic model of shamanism is therefore useful as a free frame of intellectual inspiration. Their usefulness decreases abruptly when we treat them as a summary of knowledge about shamanism. I argue that in modern research, it is certainly necessary to take a critical approach to individual statements and holistic assumptions that have grown around shamanism for decades.